The Influence of Competence, Training, and Work Culture on Leadership: A Systematic Literature Review - Johan Ferdhi Yunata; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze and synthesize previous research findings on the influence of competence, training, and work culture on leadership, as well as to develop hypotheses for future empirical research. The study employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. Data were collected from peer-reviewed academic articles published in reputable national and international journals and indexed in major academic databases, including Scopus, ScienceDirect, SpringerLink, Emerald Insight, Wiley Online Library, and Google Scholar. The selected articles focused on the variables of —competence, training, work culture, and leadership—and met the predetermined inclusion criteria. Data analysis was conducted through systematic identification, screening, data extraction, and synthesis using content analysis and thematic analysis techniques. The findings indicate that competence has a positive relationship with leadership through the enhancement of individual knowledge, skills, abilities, and managerial capabilities. Training contributes to leadership development by improving employees’ competencies and leadership-related skills required to address organizational challenges. Furthermore, a positive work culture supports effective leadership by fostering a collaborative, productive, and goal-oriented organizational environment. Based on the literature review, three research hypotheses were formulated: (1) competence influences leadership, (2) training influences leadership, and (3) work culture influences leadership. These findings provide a conceptual foundation for future empirical studies aimed at examining factors that influence leadership effectiveness in various organizational settings.